Group report on Asian market opportunities in the IP door sector (China, Japan, South Korea) - Andri Yudiantoro (2013)
2N Telecommunication is seeking to form partnerships with leading China, Korea and/or Japan’s video door phones manufacturers to expand their sales network and enter the Asian Market. This could be achieved through (1) Original Equipment Manufacturers (OEM) partnerships, (2) leveraging on partner’s distribution networks or (3) supplying partnered companies with niche technology or components. While our initial task was to assist 2N in establishing contacts with the selected Asian companies, we included a selection framework and understanding of Asian culture for 2N’s perusal. This report would highlight what the team had accomplished and provide recommendations on the way ahead.